STERILE INSECT TECHNIQUE TO COMBAT DENGUE - Karthikeyan, Lekha (LIFE: International Journal of Health and Life-Sciences, 2016)
Global warming and globalization indicate the next biggest challenge is zoonotic diseases. Dengue is one of the fastest growing tropical pandemic in the world. There are no approved vaccines for the dengue virus. Prevention thus depends on control of and protection from the bites of the mosquito that transmits it, the dengue mosquito, and Aedes aegypti. Existing methods of controlling the dengue mosquito, which include spraying or fogging using chemical pesticides, have failed to stop the spread of the disease. This is partly because the mosquitoes have developed resistance and also because the Aedes aegypti mosquito lives in and around human habitation. In countries where the human-vector interaction cannot be reduced in a short period of time, Sterile Insect Technique maybe the best and most environment friendly way to prevent the spread of this fast growing pandemic.